2013
DOI: 10.1159/000350765
|View full text |Cite
|
Sign up to set email alerts
|

Organic Chemicals in Diesel Exhaust Particles Enhance Picryl Chloride-Induced Atopic Dermatitis in NC/Nga Mice

Abstract: Background: Diesel exhaust particles (DEP) have been reported to worsen allergic airway inflammation in mice. Recently, the organic chemical components of DEP (DEP-OC) were found to be important contributors to the aggravation of allergic airway inflammation in mice. The purpose of this study was to examine the effects of DEP-OC on atopic dermatitis (AD)-like skin lesions induced by picryl chloride (PiCl) in NC/Nga mice. Methods: DEP were extracted with benzene/ethanol, and the soluble organic fraction formed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 81 publications
0
6
0
Order By: Relevance
“…One study investigated the effect of diesel exhaust particle (DEP); they also suggested that DEP was associated with atopic dermatitis in mouse models [47].…”
Section: Discussionmentioning
confidence: 99%
“…One study investigated the effect of diesel exhaust particle (DEP); they also suggested that DEP was associated with atopic dermatitis in mouse models [47].…”
Section: Discussionmentioning
confidence: 99%
“…In vivo, the activation of the inflammatory cascade was observed through activation of NF-κB signaling with a resulting increased expression of pro-inflammatory cytokines upon topical exposure to PM [121,122,169]. Additionally, an increase in epidermal thickness (i.e., an indicator for activation of the inflammatory cascade) and neutrophil infiltration was observed [121,168,179,226]. [233]…”
Section: Pm-induced Activation Of Nf-κbmentioning
confidence: 99%
“…This indicates that PM can aggravate symptoms from skin diseases with an already existing disrupted skin barrier like AE, supporting the epidemiological evidence that airborne PM can aggravate AE symptoms. Moreover, in AE mice models, topical application with the soluble phase of diesel PM (e.g., PAHs), resulted in increased lesion formation and increased immunoglobulin E (IgE) levels [226].…”
Section: Pm-induced Activation Of Nf-κbmentioning
confidence: 99%
“…This effect suggests that PM is correlated with the symptoms of skin conditions, such as atopic eczema (AE), which has a disrupted skin barrier (24,83). Additionally, topical administration of the soluble PAHs from diesel fuel exacerbates lesion formation and increases immunoglobulin E levels in AE mouse models (84).…”
Section: Effect Of Pm 25 On Differentiation and Effector Functions Of...mentioning
confidence: 99%
“…Acute epidermal thickening and dermal inflammation seen in skin with damaged barriers raises the possibility that PM 2.5 provokes an inflammatory reaction, leading to more skin damage (91). Repeated PM 2.5 application can cause severe dermal inflammation with mostly neutrophil infiltration, increasing the severity of inflammatory skin diseases (84,91).…”
Section: Pm-induced Nlrp3 Inflammasome Activationmentioning
confidence: 99%